We have a religion : the 1920s Pueblo Indian dance controversy and American religious freedom - Wenger, Tisa Joy, 1969- (Book collections on Project MUSE., 2009)
For Native Americans, religious freedom has been an elusive goal. From nineteenth-century bans on Indigenous ceremonial practices to twenty-first-century legal battles over sacred lands, peyote use, and hunting practices, the U.S. government has often acted as if Indian traditions were somehow not truly religious and therefore not eligible for the constitutional protections of the First Amendment. In this book, Tisa Wenger shows that cultural notions about what constitutes "religion" are crucial to public debates over religious freedom. In the 1920s, Pueblo Indian leaders in New Mexico